2012
DOI: 10.3176/oil.2012.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Lead and Cadmium Ions From Aqueous Solutions by Modified Oil Shale Ash

Abstract: Oil shale ash, which is a by-product from oil shale processing, was converted into an adsorbent by alkali hydrothermal activation using sodium hydroxide. The alkali-treated ash was studied for its capacity to remove lead and cadmium ions from aqueous solutions. The results of the study showed that the adsorption of lead and cadmium ions by the modified oil shale ash depended on adsorbent concentration, ash particle size, contact time and pH of solution. When the initial concentration of an aqueous solution was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…So that, higher reaction time of 24 h is not recommended for shale. Similar trails have been done [21] using alkali-treated oil shale ash as adsorbent to remove lead and cadmium ions from aqueous solutions. They reported that adsorption of lead and cadmium ions by the modified oil shale ash depended on adsorbent concentration, ash particle size, contact time and pH of solution.…”
Section: Shalementioning
confidence: 72%
“…So that, higher reaction time of 24 h is not recommended for shale. Similar trails have been done [21] using alkali-treated oil shale ash as adsorbent to remove lead and cadmium ions from aqueous solutions. They reported that adsorption of lead and cadmium ions by the modified oil shale ash depended on adsorbent concentration, ash particle size, contact time and pH of solution.…”
Section: Shalementioning
confidence: 72%
“…The empirical proposed model of the two-parameter Langmuir isotherm for gas-solid physical interaction is employed for different adsorbents [4][5][6]28]. The proposed model isotherm that can be written in its linear form which is amenable to linear kinetics analysis is:…”
Section: Langmuir Isothermmentioning
confidence: 99%
“…There are two types of adsorption isotherms most frequently used by researchers. The Langmuir and Freundlich adsorption isotherm models were employed to analyze the experimental data [5,28]. The Langmuir isotherm model, Equation (1), is the most widely used equation for modeling equilibrium data in solid-liquid adsorption systems.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of OSA-based adsorbents has also been extensively studied. An adsorbent made of OSA after alkali hydrothermal activation using sodium hydroxide had an adsorption capacity of 9 and 12 mg/g for the removal of lead and cadmium ions from aqueous solutions, respectively [10]. The maximum loading capacity of pesticides Deltamethrin and Lambda-Cyhalothrin from aqueous solutions by OSA was as high as 11.4 and 8.6 mg/g, respectively [11].…”
Section: Introductionmentioning
confidence: 99%